Educação das relações étnico-raciais : processos educativos decorrentes de uma intervenção com africanidades - Denzin, Aline de Souza (Universidade Federal de São Carlos, 2018)
The education of ethnic and race relations has been shown as an effective way to fight against racism and the discrimination existing in daily life of Brazilian Society, practices supported by the permanence of the myth of racial democracy as the denial speech of racial exclusion and inequality that exist in Brazil. To fight against the racism denial, understanding it as having a social and historical foundation, resulting in a process of a colonial speech internalization that seeks justify the hierarchy and supremacy of certain groups above others, it is what is suggested by this Doctorate research to accomplish an intervention with Africanities for the education of ethnic and race relations. Driven by the diversity problematization and dialogs, this study pursued identify and understand the educational process resulted on an Africanity intervention for the education of ethnic and race relations occurring in partnerships of the Projects: “Experiences in Leisure Diversified Activities” and “More than Soccer”. For this, a qualitative approach investigation was developed, with phenomenological inspiration, and all data shown in this work were collect in daily field records and conversation circles. From the data analysis process, two categories emerged: A) Knowing to recognize and recognizing to know; B) Me, others and the ethic and race diversity. Starting with the investigation made, it was realized that the implementation of an intervention with Africanities enabled opportunities for talks and proposition that contributed with knowing and recognizing other ways to be in the world with one another, practicing respect to all differences in a group coexistence.
Education of ethnic-racial relations : educational processes resulting from an intervention with africanities
Keywords: Processos educativos; Educação das relações étnico-raciais; Africanidades; Educational process; Education of ethnic and race relations; Africanities; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM